Study on Discriminating Flue-Cured Tobacco by Volatile Compounds Related to Geographical Origin and Cultivar - Liu, Lei; Huang, Yubi; Wang, Jun; Tang, Zongxiang; Lu, Liming; Wu, Renjun; Lei, Qiang (Asian Journal of Chemistry, 2013)
To distinguish the geographical origins and cultivars of flue-cured tobacco, 35 samples cultivated in three districts (Liangshan, Yibin and Gunagyuan) of Sichuan Province (southwest of China) were collected. Volatile compounds were analyzed with gas chromatography/mass spectrometry (GC/MS) and 56 different volatile compounds were tentatively identified and semi-quantified. The data was subjected to SIMCA-P+13.0 Software. Principal component analysis (PCA) and partial least squares discrimination analysis (PLS-DA) were used to predict the tobacco’s geographical origin or cultivar using soft independent modeling of class analogy (SIMCA) statistical techniques. Both PCA and PLS-DA indicate that all samples could be classified into three clusters coincident to the three geographical origins. The PLS-DA have an average recognition ability of 91.4 %. However, analysis on discriminating tobacco cultivars by volatiles revealed that it is difficult to find any volatile as a distinctive mark to identify these six tobacco cultivars cultured in Sichuan Province.